Impact of covid-19 on mental health and aging - Priyanka Sharma (Elsevier, 2021)
The potential ramifications of the COVID-19 pandemic on the population's mental health are a rising global concern. Both at the individual and community level, the erratic and uncertain COVID-19 outbreak has the prospective to exhibit a detrimental effect on psychological health and aging. At present, various measures are dedicated to the parameters like awareness of epidemiology, clinical aspects, mode of transmission, counteracting the spread of the infection, and public health problems, although this initiative has neglected critical mental health concerns. This study is to investigate the outbreak to study the level of harmful effects on mental health and its crosstalk with aging. Global execution of preventive, control measures and resilience establishment are challenging factors whereas reformed lifestyle such as lockdown, coping with self-isolation, quarantine, social distancing, and post-traumatic stress disorders are alarming. Hallmarks of aging which interact with each other, have been suggested to affect the healthspan in aged adults, possibly due to attenuated immunity. Among various hallmarks, we concentrated on those that show direct or indirect interaction with viral infections, comprising inflammation, genomic instability, impaired mitochondrial function, epigenetic modification, telomere attrition, and damaged autophagy. These hallmarks possibly contribute to the elicited pathophysiological responses to SARS-CoV-2 and may add an additive risk of accelerated aging post-recovery among aged adults. Here, the role of antiaging drug candidates that require main consideration in COVID-19 research is discussed briefly. In the later future, it can emerge as a potential therapeutic approach in the treatment of patients with severe infection.